Adubação orgânica com cama sobreposta suína e mineral em pastagem de Panicum maximum cv. Mombaça - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Animal production systems are directly related to the exploitation of pastures. In this context, to increase the use of pastures, increasing their productivity and bromatological quality, is found in the by-products of pig farming an alternative to reach its potential, aiming at lower production costs mainly in relation to fertilization. In this sense, this work had as objective to verify the influence of the application of deepbedding (CSS) associated to mineral fertilizers or alone, analyzing its effect on productivity and quality of Panicum maximum cv. Mombaça. The work was conducted in the experimental field of the State University of Goias, Ipameri Campus. Design was used in randomized blocks in a 2 x 5 factorial scheme with four replications, with 1 factor being 1 organic fertilization; 2 organic fertilization associated with mineral (NPK) fertilization and the second factor was the doses of CSS (0, 5, 10, 15 and 20 Mg ha-1 ), in the current humidity of the same. Fertilization was carried out in the pasture implantation, and in the plots that received associated fertilization, nitrogen fertilization was applied after each cut of the forage, being 4 cuts and 3 coverage applications. The plots area was 24 m². Samples were obtained through the free square method, where a 1 m² frame was random placed and the sample was cut, leaving a residue of 45cm. The variables analyzed were: dry matter (DM), crude protein (CP), acid detergent fiber (FDA) and neutral detergent fiber (NDF). The analysis of variance was performed, followed by the Skot Knot test (p <0.05) and for the quantitative variable, the regression analysis was performed. The applications of CSS associated to mineral fertilization presented increases from 52 to 282% DM and better results for the higher CSS doses, providing improvements in the bromatological composition. The application of CSS is beneficial to the production of pastures and the increasing applications up to the dose 20 Mg ha-1 of CSS associated with mineral fertilization presented better quantitative and qualitative results. And even the isolated fertilization with CSS presented increases in dry mass production and improvement in the bromatological quality of Panicum maximum cv. Mombaça.
Keywords: resíduo orgânico; capim mombaça; produtividade; qualidade; capim mombaça; organic residue; productivity; quality; mombaça grass; CIENCIAS AGRARIAS